ANALISIS HUBUNGAN INDEKS DEMOKRASI PROVINSI DKI JAKARTA TERHADAP TUNTUTAN BURUH PROVINSI DKI JAKARTA PADA TAHUN 2017-2020 - Nadhira Sarasvati (2024)
This research aims to determine the relationship between the DKI Jakarta Province Democracy Index and the demands of DKI Jakarta Province workers in 2017-2020 using several theories: democracy, social movements, and the democracy index. The democracy index has three main indicators: civil liberties, political rights, and democratic institutions. The method used in this research is a qualitative method with a descriptive approach, the data used is primary and secondary data obtained through interviews and documentation. The techniques used to analyze data are data reduction, data display, triangulation, and conclusions. The results of this research show that the labor actions in DKI Jakarta in 2017-2020 had an influence but were not very significant on the score of the Indonesian Democracy Index for DKI Jakarta Province. Freedom of belief, freedom of discrimination, the right to vote and be elected, political participation, decision making and government supervision, free and fair elections, the role of DPRD, the role of political parties, the role of regional government bureaucracy, and an independent judiciary are also included in the assessment of the Indonesian Democracy Index score DKI Jakarta Province. Keywords: Democracy Index, Labor Action, Democracy, Social Movement.